Phytosterol Glycosides from Olax subscorpioidea Oliv. Exhibit Cytotoxic Effects in In Vitro and In Silico Studies - Yemi Adekola Adekunle; Babatunde B. Samuel; Lutfun Nahar; Amos A. Fatokun; Satyajit D. Sarker (Pharmaceutical Sciences)
Background: Olax subscorpioidea is traditionally used to treat arthritis, cancer, diabetes, neurodegenerative disorders, and oxidative stress. This study carried out chromatographic isolation, cytotoxicity, and molecular docking studies of bioactive compounds from O. subscorpioidea. Methods: The root of O. subscorpioidea was extracted with methanol using Soxhlet extraction method. The extract was partitioned into n-hexane, dichloromethane, and methanol/water. Dichloromethane fraction was subjected to column chromatography. Bioactive compounds were isolated and their chemical structures were established by 1D and 2D nuclear magnetic resonance (NMR) spectroscopy, and by comparing their NMR data with those previously reported in the literature. MTT assay was used to evaluate the cytotoxic activity of these compounds against three human cancer cell lines: breast (MCF-7), cervical (HeLa), and colorectal (Caco-2) cell lines. Molecular docking was used to gain insights into the favourable binding conformations and energies of the compounds when interacting with ten selected cancer-related protein targets. Results: The phytochemical investigation of the extract of O. subscorpioidea afforded two sterol glycosides, stigmast-5,22-dien-3-O-β-D-glucoside (1a) and sitosterol-3-O-β-D-glucoside (1b), as a mixture. The compounds were found to be active against HeLa (IC50: 37.0±4.51 µg/mL) and MCF-7 (137.07±19.43 µg/mL) cell lines. The compounds showed strong interactions with the colchicine-binding site on the β-subunit of tubulin protein, epidermal growth factor receptor kinase domain, poly(ADP-ribose) polymerase-1, and 17β-hydroxysteroid dehydrogenase type 1 (binding energies: –10.3 and –10.0 kcal/mol; –9.3 and –9.3 kcal/mol; –9.2 and –9.2 kcal/mol; and –9.3 and –9.1 kcal/mol, respectively). Stigmast-5,22-dien-3-O-β-D-glucoside was consistently ranked higher in some of the proteins tested. The compounds stabilised in the binding sites of the proteins via hydrogen bonds and hydrophobic interactions. Conclusion: To the best of our knowledge, this is the first report of the isolation of these compounds from this plant. The cytotoxic effects of O. subscorpioidea root extract could be partly attributed to stigmast-5,22-dien-3-O-β-D-glucoside and sitosterol-3-O-β-D-glucoside.